Analisis Efisiensi dan Efektivitas Pengelolaan Keuangan Daerah Kabupaten Semarang - Hana Setyaningsih; Nabila Septiana Putri (International Forum of Researchers and Lecturers, 2024)
This research aims to assess how efficient and effective regional financial management in Semarang Regency utilizing secondary data from the Central Statistics Agency (BPS) for the years 2018–2022. Data were collected through literature study, non-behavioral observations, and data analysis using efficiency ratio and effectiveness ratio. The results showed that the level of efficiency of Semarang Regency’s regional financial management fluctuated and was generally inefficient, with a ratio ranging from 91% to 108.51%. Meanwhile, The efficiency of local financial management tends to be better, with a ratio ranging from 93.62% to 121.10%. Therefore, the Semarang Regency government is advised to increase Regional Original Revenue (PAD) and optimize the efficiency of financial management through improving the quality of human resources.